2018
DOI: 10.1136/bmjsem-2017-000296
|View full text |Cite
|
Sign up to set email alerts
|

Is recreational running associated with earlier delivery and lower birth weight in women who continue to run during pregnancy? An international retrospective cohort study of running habits of 1293 female runners during pregnancy

Abstract: BackgroundIncreasingly, women of reproductive age participate in recreational running, but its impact on pregnancy outcome is unknown. We investigated whether running affects gestational age at delivery and birth weight as indicators of cervical integrity and placental function, respectively.Methods1293 female participants were recruited from parkrun, which organises weekly runs involving 1.25 million runners across 450 parks worldwide. Those under 16 or unable to provide outcome data were excluded. Women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…Bell, et al [35] identified that frequency of vigorous intensity exercise may relate to birth weight, with findings indicating a decrease in birth weight with increasing number of exercise sessions (3 sessions = 3682 g birth weight, and 5/6/7 sessions = 3049 g birth weight). On the other hand, the study by Kuhrt, et al [43] showed that neither average weekly kilometers (i.e., volume), or trimester that women ran to, influenced birth weight percentiles. The retrospective survey by Zeanah and Schlosser [44] also showed no effect of higher volume (> 80 min/week) or higher intensity (> 150 bpm) exercise during third trimester, on birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Bell, et al [35] identified that frequency of vigorous intensity exercise may relate to birth weight, with findings indicating a decrease in birth weight with increasing number of exercise sessions (3 sessions = 3682 g birth weight, and 5/6/7 sessions = 3049 g birth weight). On the other hand, the study by Kuhrt, et al [43] showed that neither average weekly kilometers (i.e., volume), or trimester that women ran to, influenced birth weight percentiles. The retrospective survey by Zeanah and Schlosser [44] also showed no effect of higher volume (> 80 min/week) or higher intensity (> 150 bpm) exercise during third trimester, on birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Yet females are often concerned about causing harm to their baby, which can stop engagement with running 30 . However, running and/or aerobic exercise during pregnancy is not associated with an increased risk of preterm birth or reduction in gestational age at delivery 31,32 . It is therefore essential that clear messages are provided to pregnant females regarding the benefits of exercise and guidelines are updated to reflect empirical evidence 33 .…”
Section: Factors Contributing To Postpartum Return-to-runningmentioning
confidence: 98%
“…Aber kann diese Form des Sports auch unbedenklich in der Schwangerschaft fortgesetzt werden? Eine britische Studiengruppe wertete hierzu Schwangerschafts-und Geburtsverläufe von insgesamt 1293 Schwangeren aus, welche vor ihrer Schwangerschaft regelmäßig im Laufsport aktiv waren [5]. 579 (44 %) der Schwangeren hörten mit dem Laufsport bei Feststellung der Schwangerschaft auf.…”
Section: Laufen In Der Schwangerschaftunclassified
“…In der Anstrengungsphase wurden bei allen Schwangeren unregelmäßige Uteruskontraktionen aufgezeichnet, die jedoch in der Meditations-und Ruhephase nicht mehr auftraten [6]. Im Vergleich zu nicht depressiven Schwangeren weisen depressive Schwangere zudem ein erhöhtes Risiko für das Auftreten einer postpartalen Depression, verminderten Sexualerlebens sowie postpartalen Stress auf [5]. 20 % aller Schwangeren entwickeln eine postpartale Depression.…”
Section: Yoga In Der Schwangerschaftunclassified